Pengaruh Media Ular Tangga Pintar terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas II - Rahma Widi Ardianingtyas; Veryliana Purnamasari; Hartati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to determine the influence of UPIN (Smart Snakes and Ladders) media on the learning outcomes of students with Pancasila Education class II at SDN Pedurungan Lor 02. UPIN is a learning media with a snakes and ladders game system but has a special feature, namely that at a certain number towards the finish there is a question card containing questions. mystery regarding Pancasila material. The material taken was the content of Pancasila Education Unit 1. The method used is a quantitative experimental one group pretest-posttest design with paired sample, a saturated sample type, while the data analysis technique is the T-Test. The results of this research show that the use of UPIN media in Pancasila Unit 1 class II material at SDN Pedurungan Lor 02 has an influence on student learning outcomes. This data was obtained from the results of the paired sample T-Test in the SPSS v.26 application. This is proven by the results of the paired sample T-Test with a significance of 0.000, which means H0 is rejected and Ha is accepted. Based on these data, it can be concluded that the use of UPIN media has proven to have an influence on the learning outcomes of students.